Bentuk Tindakan Kejahatan Kriminal Terhadap Buruh Pabrik Perempuan di Indonesia - Rumadan, Salmawati (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
AbstractCrimes often involve women as objects of gender injustice that occurs between men and women as a result of which women do not get their proper place as working subjects, especially in Indonesia. The type of research method used is library research, library research, namely research that collects data through collecting data from various literature. The method or method used to collect data is a type of research. Qualitative research methods are research methods used to examine the condition of scientific objects. The problems that the author examines include, firstly, what forms of violence occur against female factory workers, secondly, how to resolve the violence experienced by female factory workers. The aim, firstly, is to find out what forms of violence occur against female factory workers, secondly, to find out how to resolve the violence experienced by female factory workers. Results, first. It was found that there was a form of discrimination against female workers, female workers were given high working hours and treatment was not the same as men, women were forced to work longer hours and the salary or wages they received were very minimal. Not only that, female workers were also experience sexual harassment at work. Second . Handling cases of violence against women include efforts made including compensation, restitution, compensation, and protection efforts carried out by the Ministry of Women's Empowerment and Child Protection (Kemen PPPA) or efforts made by establishing Women Workers Protection Houses in the work environment through PPPA number 1 of 2023 concerning the provision of protective housing for female workers in the workplace AbstrakTindakan kejahatan sering kali melibatkan perempuan sebagai objek ketidakadilan gender yang terjadi antara laki-laki dengan perempuan alhasil perempuan tidak mendapakan tempat sebagaimana mestinya sebagai subyek pekerja terutama di Indonesia. Jenis metode penelitian yang di gunakan adalah penelitian pustaka, penelitian pustaka yaitu penelitian yang mengumpulan data melalui penghimpunan data dari berbagai literatur. Metode atau cara yang digunakan dalam mengambil data yakni menggunakan jenis penelitian, Metode penelitian kualitatif adalah metode penelitian yang digunakan untuk meneliti pada kondisi obyek ilmiah. Masalah yang di teliti penulis antara lain pertama, Bagaimana bentuk kekerasan yang terjadi pada buruh pabrik perempuan, kedua Bagaimaan upaya Penyelesaian dari kekerasan yang dialami buruh pabrik perempuan. Tujuan, pertama untuk mengetahui bagaimana bentuk kekerasan yang terjadi pada buruh pabrik perempuan, kedua Untuk mengetahu bagaimana upaya penyelesaian dari kekerasan yang di alami buruh pabrik perempuan. Hasil, pertama . ditemukan adanya bentuk diksriminasi terhadap pekerja perempuan, pekerja perempuan diberikan waktu jam kerja yang tinggi dan perlakuan yang tidak sama dengan laki-laki, perempuan dipaksakan bekerja dengan jam waktu yang lebih lama dan gaji atau upah yang didapatkan sangatlah minim tidak hanya itu saja pekerja perempuan juga mendapatkan perlakuan pelecehan seksual ditempat kerja. Kedua . Menangani kasus kekerasan terhadap perempuan diantaranya upaya yang dilakukan diantaranya ganti rugi, restitusi, kompensasi, dan upaya perlindungan yang dilakukan oleh Kementrian Pemberdayaan Perempuan dan Perlindungan Anak ( Kemen PPPA ) salah stau upaya yang dilakukan dengan membentuk Rumah Perlindungan Pekerja Perempuan di lingkungan kerja melalui PPPA nomor 1 Tahun 2023 tentang penyediaan rumah perlindungan pekerja perempuan di tempat kerja